Perbandingan Model Characteristic Drying Rate Curve dan Reaction Engineering Approach Berdasarkan Hasil Eksperimen Pengeringan Mango Tissues - Johannes Martua Hutagalung (Universitas Insan Cendekia Mandiri, 2019)
Dry Processing was generally consist of two model mathematics, emphirical and mechanistic model. CDRC (Characteristic Drying Rate Curve) and REA (Reaction Engineering Approach) are one of mechanistic model to find physic condition in all term, which is emphirical model hasn’t. The results obtained by simulation are shown with the temperature profile and the moisture content of mango tissues that has previously been validated according to the literature. Mean square error and explained variation value showed similarity value between moisture content and temperature. Experiment data for REA using drying temperature at 338K and Y at 0,0134kg H2O/kg dry air. CDRC is divided by two approaching model, Constant Rate Period (CRP) and Falling Rate Period (FRP) at temperature 338K. To find the relative activation energy as amount of losing moisture content, temperature used at 328K. The result showed are CDRC and REA model relatively similar, which is CDRC closer to experiment data. For drying curve, moisture content of mango tissues is descending exponentially at the time of drying. But for temperature curve against time of drying, temperature of mango tissues is ascending exponentially.